Decision Research on Patent Licensing of Original Manufacturers and Technology Innovation of Independent Remanufacturers. Issue 2 (February 2020) - Sheng, Xin
Abstract: The innovation of remanufacturing technology is an effective way to keep the cost advantage of reproducts, and patent licensing facilitates the production of reproducts by independent remanufacturers. Considering people's different preferences for reproducts and new products, we first construct an evolutionary game composed of original manufacturers and independent remanufacturers based on the theory and method of evolutionary game. Next, we study the evolutionary stable point and the influence factors of patent licensing and remanufacturing technology innovation strategy selection by Jacobian matrix. Finally, the model conclusion is verified by numerical analysis. The research shows that when the innovation level of remanufacturing technology is within a certain threshold, independent remanufacturers ultimately choose the technology innovation strategy, while original manufacturers always ultimately choose the patent licensing strategy and it is not affected by the innovation level of remanufacturing technology.